A sociological investigation of the effect of cell phone use on students' academic, psychological, and socio-psychological performance - Tang, Xiaoping; Shen, Zijun; Khan, Muhammad Idrees; Wang, Qiong (Frontiers in Psychology, 2025)
This research investigates the relationship between the use of mobile phones in terms of the academic performance and mental wellbeing of the students who are attending two universities and related high schools in Guizhou province, China. The research aims at gaining insight as to the nature of the relationship between mobile phone use and students' academic, psychological and socio-psychological experiences by using a quantitative cross-sectional survey design. A sample of 300 students (150 students from Guizhou Normal University and 150 from Guizhou University) was chosen for the present study. Information provided by respondents was based on a structured questionnaire scale using five-point Likert scale measuring issues such as mobile phone use habit, academic performance and wellbeing. To enhance the understanding of these associations, moderating variables, such as age, gender, and academic discipline (STEM vs. humanities) were specified for explaining their impact on the use and impacts of mobile phones on students. The Chi-square and Gamma tests were employed in statistical analysis to investigate the interrelationships among the study variables. The finding disclosed that excessive use of mobile phones for entertainment (social media, music, and messaging) is associated with a negative impact on academic grades and mental illnesses (Gamma = −0.09). In contrast, the use of mobile phones among the students for academic purposes such as accessing educational materials had a desirable academic implication (P = 0.01). The study underscores the need for mobile phone usage moderation to increase academic achievement and the wellbeing state.